Eu ainda estou vivo: modos de existir e novas tecnologias de comunicação - Faleiros, Fabiana Amélio (2008)
This study discusses the ways in which the technologies of communication create ways of life resulting in forms of subjectivity. In the first part of the work, we discuss the concepts of subjectivity and its links with the viewing technology, in light of concepts and studies of Michel Foucault and society of the spectacle of Guy Debord. In the second part, from the concept of Relational Aesthetics of Nicolas Bourriaud, in dialogue with the work of Dominique Gonzalez-Foerster, seeking to show how this artist create the singularization of the relationship with the spaces shared through your project in video and film Parc Central. In the third part of the work, dialoguing with On Kawara, with focus on the work I am still alive - series of telegrams made from 1969. Thus, it is sought to understand how these two artists, each one in their own way, are interrelated the singularization of subjectivation processes from speaking in first person. In the fourth part we intended to create tensions between that sentence of On Kawara in the context of permanent connection of the subject in the contemporary through an "action" of the author in the city of Sao Paulo, which included posters with the phrase "I am still alive" and distribution of a video by e-mail. Confronting this "action" with the authors and artists studied, the conclusions indicates that it is through interventions in the ways of life homogenous created by the new technologies of communication that we can create spaces for singularization of contemporary subjectivity